The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/rs14041019
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Traits Estimation and Preliminary Yield Assessment in Different Phenophases of Wheat Breeding Experiment Based on UAV Multispectral Images

Abstract: The utility of unmanned aerial vehicles (UAV) imagery in retrieving phenotypic data to support plant breeding research has been a topic of increasing interest in recent years. The advantages of image-based phenotyping are related to the high spatial and temporal resolution of the retrieved data and the non-destructive and rapid method of data acquisition. This study trains parametric and nonparametric regression models to retrieve leaf area index (LAI), fraction of absorbed photosynthetically active radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 75 publications
5
17
0
Order By: Relevance
“…The results revealed that repRVI performed best in grain yield assessment at the LGF stage, which is consistent with previous studies ( Hassan et al., 2019 ; Fei et al., 2021a ; Fei et al., 2021b ; Ganeva et al., 2022 ), because the LGF stage is close to maturity and the information in the UAVs field of view is mainly provided by the mature spikes. The signal is minimally affected by moisture and other green parts of the rice plant.…”
Section: Discussionsupporting
confidence: 91%
“…The results revealed that repRVI performed best in grain yield assessment at the LGF stage, which is consistent with previous studies ( Hassan et al., 2019 ; Fei et al., 2021a ; Fei et al., 2021b ; Ganeva et al., 2022 ), because the LGF stage is close to maturity and the information in the UAVs field of view is mainly provided by the mature spikes. The signal is minimally affected by moisture and other green parts of the rice plant.…”
Section: Discussionsupporting
confidence: 91%
“…The nonparametric models performed better than the parametric ones in predicting GY. This result was in agreement with other studies, which have shown the superiority of machine learning algorithms over VI-based regression models for predicting crop traits [77,78].…”
Section: Parameterssupporting
confidence: 93%
“…According to previous studies, many ML models (such as RR, RF, SVM, and Cubist) have been successfully applied as tools for early crop phenotype estimation [13,14,70,71]. In the current study, four algorithms (SVM, RR, KNN, and PLS) were used to construct the yield estimation models.…”
Section: Effects Of Different ML Algorithms On Yield Estimation Modelmentioning
confidence: 99%